Hubungan Obesitas dengan Tekanan Darah Mahasiswa Kepaniteraan Klinik Tatap Muka pada Era Pandemi Covid-19 Di Fakultas Kedokteran Unversitas Kristen Indonesia - Louisa Ariantje Langi; Dopang Adrianto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Stay at home during the COVID-19 pandemic has resulted increase incidence of obesity among students. Obesity causes increase release of free fatty acids and sympathomimetics in body and resulting blood pressure Increased blood pressure can trigger various comorbidities such as stroke and acute coronary syndrome. This research paper to determine impact of obesity to blood pressure. This research paper using cross sectional method. Samples were taken using consecutive sampling of 61 students. Data is taken from primary data and secondary data obtained from medical students hands on at FK UKI period 26 April 2021 until 22 May 2021. Paired t-test found a significant difference between body weight before and during the COVID-19 pandemic (p=0,000; p<0,05). Prevalence ratio test found a family history of obesity and hypertension as risk factors for obesity and high blood pressure (PR = 4,8; 2,19; PR> 1). The Mann-Whiteney test found sports had no significant relationship between body mass index (p = 0.925; p> 0.05) and smoking had a significant relationship with blood pressure (p = 0.004; p <0.05). The Spearman correlation test found a significant relationship between obesity and blood pressure (p = 0.003; p <0.05; r = 0.379). There is a significant relationship between obesity and blood pressure in face-to-face clinical clerkship students, the more obese the person is, the more risk of suffering from hypertension.